2011
DOI: 10.1051/0004-6361/201015639
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and geometrical study of the Be stars 48 Persei andψPersei with the VEGA/CHARA interferometer

Abstract: Context. Five different physical processes might be responsible for the formation of decretion disks around Be stars: fast rotation of the star, stellar pulsations, binarity, stellar winds, and magnetic fields. Our observations indicate that fast rotation seems to produce a disk in Keplerian rotation, at least in the specific case of the two stars observed. We do not know if this observational result is a generality or not. Aims. We measure the size, orientation, shape, and kinematics of the disks around 2 Be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 43 publications
5
63
0
8
Order By: Relevance
“…The difference mainly originates from a saturation effect of the photon-counting camera in the emission line. After careful testing, we found that the saturation does not affect the interferometric measurements (Delaa et al 2011).…”
Section: Spectramentioning
confidence: 92%
“…The difference mainly originates from a saturation effect of the photon-counting camera in the emission line. After careful testing, we found that the saturation does not affect the interferometric measurements (Delaa et al 2011).…”
Section: Spectramentioning
confidence: 92%
“…Some examples of differential visibilities and phases for the best-fit model for various baselines between 32 and 278 m are plotted in Fig 5, bottom part. As already explained in Delaa et al (2011), phase variations for baselines overresolving the object (i.e., 60 m in the major-axis orientation and 200 m in the minor-axis one in the case of ϕ Persei) are only poorly fitted. The jumps seen for some baselines might be either due to inhomogeneity in the disk or to VEGA data reduction biases at very low visibility.…”
Section: Spectrally Resolved Hα Data and Model Fittingmentioning
confidence: 92%
“…The photoncounting detectors of VEGA suffer from a local saturation effect in presence of bright spectral lines that attenuates the line intensity. This nonlinearity in the photometric response of the detector does not generate bias in the derived complex visibilities as explained by Delaa et al (2011). To model the spectrally resolved visibility and differential phase in the Hα emission line, we used the simple kinematic model developed for fast model-fitting of a geometrically and optically thin equatorial disk in rotation described in detail by Delaa et al (2011) and Meilland et al (2012).…”
Section: Spectrally Resolved Hα Data and Model Fittingmentioning
confidence: 99%
“…Meilland et al (2012) found a mean value of ω = 0.95 for a sample of eight Be stars, considering V sin i and V crit from Frémat et al (2005) but i measurements derived from interferometry. Delaa et al (2011) deduced from interferometric observations of Be stars 48 Per and Ψ Per that both stars rotate at nearly critical rotation. Therefore, the question to which extent Be stars are really critically rotating stars is not settled yet.…”
Section: Possible Link Between Very Rapid Rotationmentioning
confidence: 99%